2010
DOI: 10.1038/ng.648
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of esophageal squamous cell carcinoma in Chinese subjects identifies a susceptibility locus at PLCE1

Abstract: We performed a genome-wide association study of esophageal squamous cell carcinoma (ESCC) by genotyping 1,077 individuals with ESCC and 1,733 control subjects of Chinese Han descent. We selected 18 promising SNPs for replication in an additional 7,673 cases of ESCC and 11,013 control subjects of Chinese Han descent and 303 cases of ESCC and 537 control subjects of Chinese Uygur-Kazakh descent. We identified two previously unknown susceptibility loci for ESCC: PLCE1 at 10q23 (P(Han combined for ESCC) = 7.46 x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
206
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 377 publications
(231 citation statements)
references
References 26 publications
13
206
2
3
Order By: Relevance
“…The genome-wide association studies (GWAS) has emerged as a powerful and successful tool to identify common disease alleles by using high-throughput genotyping technology to interrogate a large number of tagging single nucleotide polymorphisms (SNPs) that serve as surrogates for untested common SNPs across the genome. So far, GWAS of esophageal cancers including ESCC in individuals of European and Japanese ancestry, have shown that variants in ADH genes and/or ALDH2 are associated with risk of ESCC [55][56][57][58] . More recently, Wu et al further reported that nine new ESCC susceptibility loci, of which seven, at chromosomes 4q23, 16q12.1, 17q21, 22q12, 3q27, 17p13 and 18p11, had a significant marginal effect (P = 1.78 × 10 -39 to P = 2.49 × 10 -11 ) and two of which, at 2q22 and 13q33, had a significant association only in the gene-alcohol drinking interaction [gene-environment interaction P (PG × E) = 4.39 × 10 -11 and PG × E = 4.80 × 10 -8…”
Section: The Effects Of Chronic Irritation and Inflammation On Squamomentioning
confidence: 99%
“…The genome-wide association studies (GWAS) has emerged as a powerful and successful tool to identify common disease alleles by using high-throughput genotyping technology to interrogate a large number of tagging single nucleotide polymorphisms (SNPs) that serve as surrogates for untested common SNPs across the genome. So far, GWAS of esophageal cancers including ESCC in individuals of European and Japanese ancestry, have shown that variants in ADH genes and/or ALDH2 are associated with risk of ESCC [55][56][57][58] . More recently, Wu et al further reported that nine new ESCC susceptibility loci, of which seven, at chromosomes 4q23, 16q12.1, 17q21, 22q12, 3q27, 17p13 and 18p11, had a significant marginal effect (P = 1.78 × 10 -39 to P = 2.49 × 10 -11 ) and two of which, at 2q22 and 13q33, had a significant association only in the gene-alcohol drinking interaction [gene-environment interaction P (PG × E) = 4.39 × 10 -11 and PG × E = 4.80 × 10 -8…”
Section: The Effects Of Chronic Irritation and Inflammation On Squamomentioning
confidence: 99%
“…In 2010, as part of the genome-wide association study (GWAS), we investigated 25,000 patients as well as healthy controls for susceptibility loci to esophageal squamous cell carcinoma (ESCC), and identified C20orf54 as 1 of these susceptibility loci [1]. C20orf54, known as human riboflavin transporter 2, has a messenger RNA (mRNA) that comprises 2,716 bp (NM_033409.3) and encodes an open reading frame protein of 469 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Low selenium nutritional status, as reflected in the low toenail selenium content, was also associated with risk of GCA and ESCC in the Netherlands Cohort Study [75]. In this area, some genetic susceptibility factors are shared by GCA and ESCC, as described above [25,26]. …”
Section: Esophageal Adenocarcinomamentioning
confidence: 99%
“…A previous genome-wide association study (GWAS) in Japan showed that functional variants in alcohol dehydrogenase IB and aldehyde dehydrogenase 2, coupled with alcohol drinking and smoking, synergistically enhanced the risk of EC [24]. A recent, large GWAS in China identified susceptibility loci at PLCE1 (regulating cell growth, differentiation, apoptosis and angiogenesis) and C20orf54 (involved in riboflavin transport) for both ESCC and GCA [25]. The shared susceptibility locus in PLCE1 for ESCC and GCA in the Chinese population was also observed by Abnet et al [26].…”
Section: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%